Seeing the World Topsy-Turvy: The Primary Role of Kinematics in Biological Motion Inversion Effects. (April 2014) - Fitzgerald, Sue-Anne; Brooks, Anna; van der Zwan, Rick; Blair, Duncan
Physical inversion of whole or partial human body representations typically has catastrophic consequences on the observer's ability to perform visual processing tasks. Explanations usually focus on the effects of inversion on the visual system's ability to exploit configural or structural relationships, but more recently have also implicated motion or kinematic cue processing. Here, we systematically tested the role of both on perceptions of sex from upright and inverted point-light walkers. Our data suggest that inversion results in systematic degradations of the processing of kinematic cues. Specifically and intriguingly, they reveal sex-based kinematic differences: Kinematics characteristic of females generally are resistant to inversion effects, while those of males drive systematic sex misperceptions . Implications of the findings are discussed.